Finding the patient in patient safety. (November 2013) - Hor, Su-yin; Godbold, Natalya; Collier, Aileen; Iedema, Rick
In the last decade, the field of patient safety has grappled with the complexity of health-care systems by attending to the activity of frontline clinicians. This article extends the field by highlighting the activity of patients and their carers in determining the safety of these systems. We draw on data from three studies exploring patients' accounts of their health-care experiences in Australia and internationally, to show how patients and carers are currently contributing to the safety of their own care. Furthermore, we emphasise the importance of patient–clinician collaboration in ensuring the success of these activities. We argue that it is no longer sufficient to discuss if patients should be involved with ensuring their own safety. Given that patients are already involved, we propose a new conceptualisation of safety and systems that acknowledges their involvement and supports patient–provider collaboration to achieve safer care.